Comparison of marginal and internal fit of 5-unit zirconia fixed dental prostheses fabricated with CAD/CAM technology using direct and indirect digital scans - Irem Gokce Uluc; Mustafa Baris Guncu; Guliz Aktas; Ilser Turkyilmaz (Elsevier, 2022)
Background/purpose: Advancements in digital dentistry and the development of intraoral scanners (IOS) have provided clinicians with an accurate and efficient alternative to analog impressions. The aim of this study was to assess the accuracy of the marginal and internal fit of 5-unit monolithic zirconia fixed dental prostheses (FDPs) fabricated with CAD/CAM technology using direct and indirect digitalization methods. Material and methods: Three teeth in a maxillary typodont model were prepared to receive a 5-unit zirconia FDP. Six different groups were created according to the type of scanner (intraoral and extraoral) and the type of workflow. For direct workflow, the typodont was scanned with two different IOS (3Shape Trios 3 [3S-IOS] and Cerec Omnicam [C-IOS]). For indirect workflow, after conventional impressions were obtained, the impressions (IMP) were scanned with two different laboratory scanners (3S-IMP and C-IMP). After the impressions were poured, the stone (STN) casts were scanned with the same laboratory scanners (3S-STN and C-STN). Sixty 5-unit monolithic zirconia FDPs (10 in each group) were designed and milled. The marginal and internal fit was assessed. Results: The mean marginal gap values were 78.2±9 μm in the IOS group, 82.6± 9 μm in the IMP group, and 82.6±9 μm in the STN group, indicating no statistically significant differences among groups (p > 0.05). The mean axial gap values were 77.7 ± 10 μm in IOS group, 83.61 ± 15 μm in the IMP group, and 84.5±9 μm in the STN group, indicating no statistically significant differences among groups (p > 0.05). Conclusion: The marginal and internal fit of 5-unit monolithic zirconia FDPs fabricated with direct and indirect digital scans were similar. The smallest gap values were observed at the marginal region while the greatest gap values were detected at the occlusal region.